Avoiding Liquidity Traps - Jess Benhabib; Stephanie Schmitt-Grohe; Martin Uribe (Rutgers University, Department of Economics, 2000)
Once the zero bound on nominal interest rates is taken into account, Taylor-type interest-rate feedback rules give rise to unintended self-fulfilling decelerating inflation paths and aggregate fluctuations driven by arbitrary revisions in expectations. These undesirable equilibria exhibit the essential features of liquidity traps, as monetary policy is ineffective in bringing about the government's goals regarding the stability of output and prices. This paper proposes several fiscal and monetary policies that preserve the appealing features of Taylor rules, such as local uniqueness of equilibrium near the inflation target, and at the same time rule out the deflationary expectations that can lead an economy into a liquidity trap.
Keywords: 330